2020
DOI: 10.1002/ece3.6548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an anthropogenic diet on indicators of physiological challenge and immunity of white ibis nestlings raised in captivity

Abstract: When wildlife forage and/or live in urban habitats, they often experience a shift in resource availability and dietary quality. Some species even use human handouts, such as bread, as well as human refuse, as a large part of their new diets; yet the influences of this nutritional shift on health and survival remain unclear. American white ibises are increasingly being seen in urban areas in Florida; they collect handouts, such as bread and other food items, from humans in parks, and are also found foraging on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…For example, future work should examine whether variation in hemoglobin concentrations among rural and suburban sparrows is associated with resting and maximum metabolic rates. Additionally, hemoglobin synthesis can be suppressed by poor nutrition (Minias, 2015), so future studies should also examine whether availability of micronutrients on the landscape influences the metabolic phenotypes of rural and suburban song sparrows (Coogan et al, 2018;Cummings et al, 2020a). Finally, to better understand the ecological relevance of varying hemoglobin levels, it is critical to understand whether hemoglobin concentration is related to breeding ecology and fitness outcomes (e.g., survival and reproductive success).…”
Section: Discussionmentioning
confidence: 99%
“…For example, future work should examine whether variation in hemoglobin concentrations among rural and suburban sparrows is associated with resting and maximum metabolic rates. Additionally, hemoglobin synthesis can be suppressed by poor nutrition (Minias, 2015), so future studies should also examine whether availability of micronutrients on the landscape influences the metabolic phenotypes of rural and suburban song sparrows (Coogan et al, 2018;Cummings et al, 2020a). Finally, to better understand the ecological relevance of varying hemoglobin levels, it is critical to understand whether hemoglobin concentration is related to breeding ecology and fitness outcomes (e.g., survival and reproductive success).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we did not estimate food quality, but food quality may have impacted condition in the birds we studied. Low‐quality food is associated with decreased measures of avian condition, such as immune function (Cummings et al, 2020) and body mass (Wright et al, 1998). Similarly, when European Starlings brought larger portions of low‐quality food, nestling growth rate was slower than when parents provided more digestible food (Wright et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Diet can also directly affect immunity without the mediation of hormones. In captive white ibis, birds that were fed anthropogenic dietary items like white bread had reduced bacterial killing ability, but corticosterone levels and the other immune parameters investigated were unaffected by diet treatment (Cummings et al 2020). Other work has found that restriction of dietary protein can limit immune activity (Lee et al 2006, Povey et al 2009) and high lipid diets can increase mortality rates during infection (Adamo 2008, Adamo et al 2010.…”
Section: Introductionmentioning
confidence: 95%